Labada laundry practices of selected Filipino middle income households in Batangas - Dimaano, Deanna Faith M.; Quiñola, Kim Agatha; Malvar, Astrud (Quezon City University of the Philippines Diliman, 2025)
This descriptive study investigated the laundry practices of middle-income Filipino households using Social Practice Theory (SPT). SPT describes how individual practices are shaped by three factors: (1) materials, the resources and technologies that enable an individual to perform a practice; (2) competences, the skills and knowledge that enable individuals to perform the practice; and (3) meanings, the ideas, perceptions, and aspirations that is behind the practice. Seven individuals responsible for household laundry were purposively selected and interviewed to gather data. The results were analyzed thematically using the three SPT factors. For the ‘material’ aspect, it was found that the participants are equipped with appliances and cleaning agents for both hand-washing and machine-washing, but not protective wear like gloves. Time for laundering was most discussed as an important resource, since the participants have to manage it with other responsibilities. For the ‘competences,’ all of the participants learned their knowledge and skills in laundering from maternal figures, such as segregation of clothing, hand wash followed by machine rinse, and use of bleach to remove stains. They continue with these methods, even if there are alternative and more sustainable techniques. And for ‘meanings,’ the participants strictly commit to their standards of cleanliness – stain-free and ‘mabango’ (fragrant). However, this is often done at the expense of their resources such as water, finances, labor and time, and the garment’s lifespan from too much bleach or scrubbing. It is also notable that hand-washing is associated with ‘masipag’ (hardworking) and ‘maayos na laba.’ (proper laundry). In light of growing concerns with unsustainable laundry, these findings show that limitations in resources and skills, as well as socio-cultural values contribute as barriers. Further research may explore how to address these barriers to promote sustainable change in laundering.
In partial fulfillment for the Degree of Bachelor of Science in Clothing Technology
Thesis
Keywords: Laundry -- Social aspects -- Philippines; Laundry -- Equipment and supplies; Laundry -- Philippines; Laundry practices; Social practice theory; Sustainable laundering